Development of Educational Game Learning Media Supported by Wordwall to Improve Student Learning Motivation in High School - Gitapramesti, Trisnandari (Universitas Negeri Padang, 2025)
Learning media is very important for the learning process, one of which is to increase students' learning motivation by using educational game media assisted by Wordwall. The lack of student learning motivation at SMA Tahuna Bangsa Palembang in physics lessons, specifically in the topics of temperature and heat. This study employs the Research and Development (R&D) method, utilizing the ADDIE development model which consists of five steps: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The effectiveness of the media was tested through pretests and posttests of learning motivation, showing an increase in the average score from 31.84 to 65.96, with an N-Gain value of 0.48 (considered moderately effective). Additionally, the results of the learning motivation questionnaire indicated an increase from 60% before the use of Wordwall, to 83% after the use of Wordwall. Thus, there is a difference in learning motivation before and after the use of the educational physics game media assisted by Wordwall.